2022
DOI: 10.1186/s12348-022-00298-y
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic manifestation after SARS-CoV-2 vaccination: a case series

Abstract: Background The aim of this report is to describe ocular side effects in patients who received one of the two COVID-19 vaccines – Astra Zeneca or Pfizer-Biontech and to contribute to the common understanding of the COVID-19 vaccination process. Results Three patients reactivated underlying herpetic disease and developed uveitis and keratitis. Two of them were vaccinated with Pfizer and one was with Astra Zeneca. Two patients were vaccinated with Pfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…A total of 65 studies were both qualitatively and quantitatively analyzed ( Table 1 ) [ 1 , 5 , 7 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ,…”
Section: Resultsmentioning
confidence: 99%
“…A total of 65 studies were both qualitatively and quantitatively analyzed ( Table 1 ) [ 1 , 5 , 7 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ,…”
Section: Resultsmentioning
confidence: 99%
“…Optic neuropathy is suspected as one of adverse events of the COVID-19 vaccine, which includes ON associated with or without demyelinating CNS diseases [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ], NA-AION [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], and NMOSD [ 8 , 9 ]. Lotan et al reviewed 14 case reports and 2 case series by electronic searches of the published literature regarding neuro-ophthalmological complications of COVID-19 vaccines and reported that optic neuritis was the most common, occurring in 61 of 76 cases (80.3%) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…We read with interest the article by Murgova et al about five patients with ophthalmologic complications after a SARS-CoV-2 vaccination [ 1 ]. Patient-1 experienced right herpetic keratitis and iridocyclitis, patient-2 left anterior uveitis, patient-3 retinal detachment, retinal necrosis, and vitritis, patient-4 anterior ischemic optic neuropathy (AION), and patient-5 left ptosis after subarachnoid bleeding (SAB) (Table 1 ) [ 1 ]. The study is promising but raises concerns that should be discussed.…”
mentioning
confidence: 99%
“…Ptosis, ophthalmoparesis, and pupillary dilatation after SAB is not uncommon and rather a neurological than an ophthalmologic complication after SAB. Unfortunately, nothing is reported about the outcome of these deficits and of SAB [ 1 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation